1978
DOI: 10.1007/bf01448352
|View full text |Cite
|
Sign up to set email alerts
|

Parental reactions to children with congenital heart disease

Abstract: Informal discussions with 260 families of children with congenital heart disease are reported. Parents raised questions concerning etiology, timing of the diagnosis, pathophysiology and symptomatology, and need for restriction. Depending upon the stage and seriousness of the disease, common parental behavior was observed. A psychological process similar to mourning is required at the time of diagnosis and at the time of corrective surgery in order to promote the family's adaptation to the child with congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 7 publications
3
25
0
Order By: Relevance
“…Parental overprotection was not found to be associated with age, sex, or heart defect complexity, which corresponds with the findings of Parker [44], as well as that of Garson and colleagues [32]. The lack of an association between parental overprotection and heart defect complexity suggests that having a child born with a chronic medical condition like CHD, regardless of severity of CHD, may elicit similar levels of parental protective behavior.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Parental overprotection was not found to be associated with age, sex, or heart defect complexity, which corresponds with the findings of Parker [44], as well as that of Garson and colleagues [32]. The lack of an association between parental overprotection and heart defect complexity suggests that having a child born with a chronic medical condition like CHD, regardless of severity of CHD, may elicit similar levels of parental protective behavior.…”
Section: Discussionsupporting
confidence: 68%
“…Linde and colleagues [31] also reported an association between increased maternal anxiety/ protection and poor emotional adjustment in children with CHD. In addition, Garson et al [32] conducted informal interviews with families of children with CHD and noted that parental overprotection appeared to be unrelated to the child's degree of heart disease severity, suggesting that the presence of any CHD may be sufficiently anxiety-provoking in some parents to elicit overprotective behaviors. However, it should be noted that protective parental behavior may represent an understandable reaction to giving birth to a "blue baby" who perhaps was not expected to reach adulthood.…”
Section: Parental Overprotectionmentioning
confidence: 96%
“…Parental mourning, chronic sorrow, hopelessness, and posttraumatic stress disorder have been identified in the literature 8,15,23,24 as potential concerns for parents of children with CHD. Whether being saddened over their child's heart defect, fearing the loss of their child, facing an uncertain future or simply letting go of control, mothers in our study found solace in Finding Meaning and Spiritual Connection.…”
Section: Discussionmentioning
confidence: 97%
“…If anger is directed toward the family, the physicians, and the mental health professionals, they may impede appropriate care and ultimately be negative for the child's health and adjustment [36]. As Garson et al [37] discovered through informal discussions with parents of children with CHD, conscious and unconscious anger can be a coping mechanism, where anger is an expression of underlying frustration and feelings of injustice and a way to react to the loss of the ''expected normal child.'' That some mothers of children with severe CHD have heightened angry feelings supports the hypothesis that they could be an especially vulnerable group that experience more stress and are in need of interventions [9].…”
Section: Means Of Anger Across Timementioning
confidence: 97%
“…These items are not geared specifically to being the caretaker of a child with a serious disease; rather, they are general statements, modified to measure an overall evaluation of life [24,37]. When mothers answer these items, we suppose that their severely sick child might not be a sufficient cause to report a low rating of life satisfaction.…”
Section: Means Of Anger Across Timementioning
confidence: 99%